Ethnomathematics and Curriculum: An Ethnographic Study in Limbu Community - Bhatta, Krishna Prasad; Kandangwa, Smiriti (Interdisciplinary Research in Education, 2022)
This study was carried out to see the indigenous practices and the hidden knowledge of mathematics in the ancientartifacts inthe Limbu community. This study aims to explore,how they internalize the phenomenon related to mathematics in their daily life. The entire research process of the study was guided by the Interpretivism paradigm followed by ethnographic design with the observation of documents and daily used artifacts which can be blended intothe local curriculum. Nepal is a multicultural, multilingual, multiethnic country with diverse flora and fauna. We have many artifacts and local mathematical practices in different communities. The purpose of this paperis to introduce the concept of Ethnomathematics and its relevance to classroom activities.This paper seeks to provide a comprehensive concept of some of the current and recent scholarly literature concerning Ethnomathematics and the applicability of Ethnomathematics as a practical teaching approach, particularly for underrepresented students.